Eksistensi perpustakaan sebelum kehadiran Islam - Sahidi Sahidi (UIN Sumatera Utara, 2018)
The library before Islam experienced a fairly dynamic development. This can be seen from the existing library in the Mesopotamian region which was originally a Sumaria as the originator of writing, until the library Telloh that developed where there are 30 thousand midrib or writing media there are also there. In that place also found some places used to memorize and there are books about religion, magic and legislation. History records that there were a number of libraries ever established by humans before the arrival of Islam in Arab and medieval Europe, this library is the Library in Mesopotamia, the Ancient Egyptian Library, the Ancient Greek Library, the Ancient Roman Library and the Library in Europe.Keywords: library, islam